2015
DOI: 10.1186/s40200-015-0183-9
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Ramadan fasting on glucose homeostasis and adiponectin levels in healthy adult males

Abstract: BackgroundAdiponectin is a hormone secreted by adipocytes during the fasting phase of the fast-fed cycle. Ramadan fasting involves prolonged fasting for up to twelve hours and thus could lead to increased secretion of adiponectin by adipocytes. However, studies on the role of adiponectin on glucose and body weight homeostasis during Ramadan fasting is still a matter of controversy. Thus the specific aim of this study was to assess the effect of fasting during Ramadan on the adiponectin levels, body weight and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
32
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(35 citation statements)
references
References 33 publications
3
32
0
Order By: Relevance
“…Mean weight was reduced slightly in Ramadan in this study. A majority of studies showed a significant decrease in mean weight in Ramadan (16,18,(20)(21)(22)(23)(24) but this was recouped in Shawwal (21,23). Shruthi et al indicated that the decrease in weight during Ramadan could be due to a reduction in fluid intake and a decline in glycogen-bound water stores (24).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Mean weight was reduced slightly in Ramadan in this study. A majority of studies showed a significant decrease in mean weight in Ramadan (16,18,(20)(21)(22)(23)(24) but this was recouped in Shawwal (21,23). Shruthi et al indicated that the decrease in weight during Ramadan could be due to a reduction in fluid intake and a decline in glycogen-bound water stores (24).…”
Section: Discussionmentioning
confidence: 99%
“…However, other studies have been conducted on non-diabetes patients and healthy subjects (11)(12)(13)(14)(15)(16). Some studies focused on the effects of Ramadan fasting on young university students among Arab and Iranian students (1,(17)(18)(19)(20)(21)(22)(23)(24). The eating habits and other physical activities of the Pakistani population during Ramadan may differ compared with the Muslim populations of Arab and other countries, therefore, there is a possibility that the effect of Ramadan fasting could be different for Pakistani university students.…”
Section: Introductionmentioning
confidence: 99%
“…Nutrients 2020, 12, 1029; doi:10.3390/nu12041029 www.mdpi.com/journal/nutrients a reduction in blood pressure and heart rate [16][17][18][19][20]; a reduction in inflammation; and protection against neurodegeneration [17][18][19][21][22][23][24][25][26][27][28][29][30].…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, it is claimed that both IF and Ramadan fasting to reduce oxidative damage and inflammation, optimize energy metabolism, and boost cellular protection (8,9). For instance, the pattern of insulin resistance-mediating adipocytokines suggests potentially beneficial metabolic effects of Ramadan fasting (10). Fasting was shown to reduce body weight and have a positive effect on lipid profile and glucose levels (11).…”
Section: Impact Of Fasting On Human Health and Diseasesmentioning
confidence: 99%